(untitled) (Studia Prawnicze / The Legal Studies, 1985)
Hegel solved the perpetual problem of the philosophy of law - the problem of a supraempirical element in law. Before him, the school of law of nature formulated a generally accepted solution of the problem, according to which there exists perpetual, invariable, valid per se law, irrespectively of positive, real, variable law. The idea of law and its reality was separated here. Hegel joined those two laws into one in which there exists and acts the ideal of law which creates it and is realized in it. It constantly develops and undergoes changes as law through the stages: thesis - antithesis - synthesis where each synthesis becomes a new thesis. Thus, freedom is the idea of law. In spite of the difficulties in the structure of this solution Hegel’s solution is still very important for the philosophy of law, first of all owing to its dialectic. Serbian philosopher of law, T. Żivanavić tried to join these two solutions - Hegel’s and that of school of nature - saying that the idea of law suddenly created the law of nature which was later on transformed into changeable national positive law